Depression and Physical Illnesses: an Update (Bangladesh Medical Journal, 2012)
Many chronic illnesses have a strong effect on an individual's mental and emotional status, and, in turn, undiagnosed mental disorders can affect a person's ability to cope with an illness and participate in the treatment and recovery process. Depression is the most common complication of almost all chronic or serious medical conditions. Major depression among persons experiencing chronic medical conditions like cardiovascular diseases, diabetes, respiratory diseases, obesity, cancer etc. increases the burden of their physical illness and somatic symptoms, causing increased functional impairment along with increased medical costs. Depression in long-term illnesses impairs ability for self -care and for maintenance of treatment regimens thus causing increased mortality. Yet, effective treatments, for depression exist. Many factors point to reasons that mental illnesses are not adequately addressed as evidenced by the literatures. Primary care services need to improve ways of identifying depression associated with particular chronic illnesses. we must develop new ways to understand the extent of this mental health problem, and optimal ways to evaluate manage and treat depression in patients with other co-morbid medical conditions. DOI: http://dx.doi.org/10.3329/bmj.v40i1.9966 BMJ 2011; 40(1): 53-58